2005
DOI: 10.1111/j.1523-1755.2005.00295.x
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure in ANCA-positive patients: A case-control study

Abstract: These results support the hypothesis that the presence of ANCA in plasma might at least partially be related to occupational exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 31 publications
3
41
0
Order By: Relevance
“…Beaudreuil et al have compared exposure intensity in 60 ANCA-positive patients, 20 with WG and 120 hospitalized, age-(± 5 years), gender-matched controls. 17 They found that patients with the highest category of silica exposure had the highest risk of ANCA positivity (OR=6.9, 95% CI: 1.33-35.1), but they found no difference in silica exposure in subject groups identified by ANCA subtype.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Beaudreuil et al have compared exposure intensity in 60 ANCA-positive patients, 20 with WG and 120 hospitalized, age-(± 5 years), gender-matched controls. 17 They found that patients with the highest category of silica exposure had the highest risk of ANCA positivity (OR=6.9, 95% CI: 1.33-35.1), but they found no difference in silica exposure in subject groups identified by ANCA subtype.…”
Section: Discussionmentioning
confidence: 96%
“…[13][14][15] The smoking prevalence in 197 patients with small vessel vasculitis and ANCA was observed to be lower than age-comparable values for the general population of Germany, suggesting that cigarette smoking could have a protective effect on disease development. 16 However, a study comparing previous or current smoking history between 60 ANCA-positive patients and 120 ANCA-negative controls did not identify an association, 17 nor did a study of 129 ANCA small vessel vasculitis cases and 109 population-based controls. 5,6 The role of environmental factors in the development of autoimmune diseases is of particular concern in Western Montana where occupational asbestos exposures have been associated with acquiring both systemic autoimmune responses and various autoimmune disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated antibodies (cPR3, plasminogen, lysosomal-associated membrane protein 2, cathepsin G, lactoferrin, azurocidin, and elastase), elevated cytokines (TNF-a, IL-17, and IL-23), reduced regulatory T cell to effective T cell ratio, alterations in CD8+ T cell transcription, dysfunctional neutrophil apoptosis, and disrupted epigenetic silencing are all possible contributors to internal neutrophil activation (1,3,5,7,22). Environmental exposures (silica and asbestos), pathogens (Staphylococcus aureus, Ross virus, and Entamoeba histolytica), or medications (propylthiouracil and hydralazine) could all provide an external stimulus for neutrophil activation (2,3,(23)(24)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Beaudreuil et al showed that exposure to silica is associated with a nearly seven-fold increased risk of being ANCA-positive [69]. ANCA, both PR3 and MPO, are detected in sera of patients with protracted infections; however, in most infections, ANCA are directed against a wide repertoire of antigens and tend to be dual [70].…”
Section: Updates In the Diagnosis And Treatment Of Vasculitismentioning
confidence: 99%